(untitled) (Fiep Bulletin - online, 2014)
The precocious wean of breast feeding is that way considered when there is an introduction or replacement of other kinds of food in the baby’s diet, before six months old. The interruption of motherly milk in that period may modify the metabolism, causing a reduction of infantile malnutrition and reduction of the respiratory’s system defense, which results the instalation of infectious processes on it. The main subject of this work is make an analysis of precocious wean influence on the respiratory’s system. Were evaluated twelve interned children in Centro de Nutrição Infantil of Foz do Iguaçu, between 2 months and one year and half years old. The results indicates that 66,6% of the children had precocious wean, being 87,5% of them malnutrited and 62,5% anaemic; 62,5% shows secretion in the higher air way and 37,5% in the lower. With these statistics, we can conclude that precocious wean can bring infantile malnutrition, anaemic and problems with the respiratory’s system, and they may be avoided or reduced by guides and constant education of a specialist team, with focus on prevention and publicity of health.